THE EFFECTIVENESS OF USING AUTHENTIC MATERIALS IN TEACHING RECOUNT TEXT TO IMPROVE STUDENTS' WRITING ABILITY: AN EXPERIMENTAL STUDY OF THE FIRST GRADE STUDENTS OF SMA PGII 1 BANDUNG - Mitha Yulinar Minhatul Maula, - (2008)
This research entitled "The Effectiveness of Using Authentic Materials in Teaching Recount Text to Improve Students' Writing Ability" is aimed at investigating whether using authentic material is effective in improving students' writing skill and finding out students' response to the use of authentic material in learning English. The subjects of this study were the students of class X-3 of SMA PGII 1 Bandung as the control group and X-5 as the experimental group. The method of this research was a quantitative research applying quasi experimental design which involved administering two kinds of instrument, writing test and questionnaire. The writing test was used to investigate student's ability in writing before and after the treatment, and the questionnaire was used to investigate student's response to the use of authentic material. The result of this study shows that after the treatment there is a significant difference on student's writing skill between the experimental and the control groups. The findings also show that there is a significant difference on the experimental group's pre-test and post-test scores. Furthermore, the result shows that there is no significant difference on the control group's pre-test and post-test scores. Moreover, the results of the questionnaire shows that the students agree that authentic material can help them to ease their writing activity. Therefore, it is concluded that authentic material is effective in improving student's writing skill.